Impact of the time interval between primary or interval surgery and adjuvant chemotherapy in ovarian cancer patients - Farolfi, Alberto; Petracci, Elisabetta; Gurioli, Giorgia; Tedaldi, Gianluca; Casanova, Claudia; Arcangeli, Valentina; Amadori, Andrea; Rosati, Marta; Stefanetti, Marco; Burgio, Salvatore Luca; Cursano, Maria Concetta; Lolli, Cristian; et al. (Frontiers in Oncology, 2023)
Introduction Primary debulking surgery (PDS), interval debulking surgery (IDS), and platinum-based chemotherapy are the current standard treatments for advanced ovarian cancer (OC). The time to initiation of adjuvant chemotherapy (TTC) could influence patient outcomes. Methods We conducted a multicenter retrospective cohort study of advanced (International Federation of Gynecology and Obstetrics (FIGO) stage III or IV) OC treated between 2014 and 2018 to assess progression-free survival (PFS) and overall survival (OS) in relation to TTC. All patients underwent a germline multigene panel for BRCA1/2 evaluation. Results Among the 83 patients who underwent PDS, a TTC ≥ 60 days was associated with a shorter PFS (hazard ratio (HR) 2.02, 95% confidence interval (CI) 1.04–3.93, p = 0.038), although this association lost statistical significance when adjusting for residual disease (HR 1.52, 95% CI 0.75–3.06, p = 0.244, for TTC and HR 2.73, 95% CI 1.50–4.96, p = 0.001, for residual disease). Among 52 IDS patients, we found no evidence of an association between TTC and clinical outcomes. Ascites, type of chemotherapy, or germline BRCA1/2 mutational status did not influence TTC and were not associated with clinical outcomes in PDS or IDS patients. Discussion In conclusion, longer TTC seems to negatively affect prognosis in patients undergoing PDS, especially those with residual disease.